Processing resources and eyewitness suggestibility - Zaragoza, Maria S. (Legal and criminological psychology, 1998)
Purpose. Two experiments were conducted to test the hypothesis that encountering or retrieving suggested information under conditions of limited, rather than full, attentional resources is likely to increase false memory for suggested events. Methods. A typical eyewitness suggestibility paradigm was employed in which participants viewed a slide sequence depicting an office theft, answered misleading questions regarding the theft, and were later tested on their memory for the source of the suggested details. In Expt 1, participants encountered the misinformation under conditions of either divided or full attention, and in Expt 2 participants were given either ample time to make the source judgment or were forced to provide source judgments very quickly. Results. The results of both experiments showed that participants who encountered (Expt 1) or retrieved (Expt 2) misleading suggestions under conditions of limited attentional resources were more likely to misattribute the suggested items to the slides and less likely to remember having encountered the suggestions in the post-event questions. Conclusions. The results support the hypothesis that limiting attentional resources impairs participants' ability to retrieve source-specifying information and increases false memory for suggested details.